Neuroligin-3: A Circuit-Specific Synapse Organizer That Shapes Normal Function and Autism Spectrum Disorder-Associated Dysfunction - Uchigashima, Motokazu; Cheung, Amy; Futai, Kensuke (Frontiers in Molecular Neuroscience, 2021)
Chemical synapses provide a vital foundation for neuron-neuron communication and overall brain function. By tethering closely apposed molecular machinery for presynaptic neurotransmitter release and postsynaptic signal transduction, circuit- and context- specific synaptic properties can drive neuronal computations for animal behavior. Trans-synaptic signaling via synaptic cell adhesion molecules (CAMs) serves as a promising mechanism to generate the molecular diversity of chemical synapses. Neuroligins (Nlgns) were discovered as postsynaptic CAMs that can bind to presynaptic CAMs like Neurexins (Nrxns) at the synaptic cleft. Among the four (Nlgn1-4) or five (Nlgn1-3, Nlgn4X and Nlgn4Y) isoforms in rodents or humans, respectively, Nlgn3 has a heterogeneous expression and function at particular subsets of chemical synapses and strong association with non-syndromic autism spectrum disorder (ASD). Several lines of evidence have suggested that the unique expression and function of Nlgn3 protein underlie circuit-specific dysfunction characteristic of non-syndromic ASD caused by the disruption of Nlgn3 gene. Furthermore, recent studies have uncovered the molecular mechanism underlying input cell-dependent expression of Nlgn3 protein at hippocampal inhibitory synapses, in which trans-synaptic signaling of specific alternatively spliced isoforms of Nlgn3 and Nrxn plays a critical role. In this review article, we overview the molecular, anatomical, and physiological knowledge about Nlgn3, focusing on the circuit-specific function of mammalian Nlgn3 and its underlying molecular mechanism. This will provide not only new insight into specific Nlgn3-mediated trans-synaptic interactions as molecular codes for synapse specification but also a better understanding of the pathophysiological basis for non-syndromic ASD associated with functional impairment in Nlgn3 gene.